Returning to Surplus: New Zealand's Post-GFC Fiscal Consolidation Experience - Dhritidyuti Bose; Renee Philip; Richard Sullivan (New Zealand Government, The Treasury, 2016)
New Zealand's fiscal outlook deteriorated following the Global Financial Crisis, and in late 2008 fiscal projections showed net government debt in New Zealand increasing from 5% of GDP to around 40% within 10 years, mostly reflecting permanently lower expectations for future tax revenue. These circumstances were compounded by the significant costs associated with the Canterbury earthquakes in 2010 and 2011. The structural deficit peaked at 4% of GDP in 2011. In 2011, the Government set a target to return the Budget to surplus by 2014/15, and stepped up its fiscal consolidation programme. A surplus was achieved in that year, and net debt has now peaked just above 25% of GDP. The surplus was achieved predominantly by slowing the growth rate of nominal spending so that expenses-to-GDP declined. The slowing in expense growth reflected a combination of factors including programme savings, efficiency savings, reprioritisation, and slower public sector wage growth. New Zealand's fiscal management approach - a combination of fixed nominal baselines for most expenditure alongside comprehensive top-down constraints on new spending through the Budget - provided effective tools for controlling expense growth. Nevertheless, the return to surplus is only the first step in fiscal consolidation and challenges remain to ensure these surpluses are sustained, and to rebuild the fiscal buffers that existed prior to 2009.
Keywords: E62; E65; H62; 330; Balanced Budget; Fiscal policy; Fiscal institutions; Fiscal Management Approach; Fiscal Policy; Fiscal Target; National Budget; Public Finance Act; Surplus; Haushaltskonsolidierung; Finanzpolitik; Haushaltsrecht; Öffentlicher Haushalt; Neuseeland